2013
DOI: 10.1001/jamaoto.2013.214
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Toxicity of Peritumoral Delivery of Nanoconjugated Cisplatin in an In Vivo Murine Model of Head and Neck Squamous Cell Carcinoma

Abstract: Importance Treatment of locally advanced head and neck squamous cell carcinoma (HNSCC) uses a multi-disciplinary approach often limited by the toxicity and drug resistance of platinum agents. Objectives To test whether a nanocarrier-conjugated cisplatin boosting locoregional drug delivery improves tumor efficacy while decreasing systemic toxicity over systemic cisplatin in a murine model of locally advanced HNSCC. Design A randomized, controlled, in vivo study compared standard cisplatin with nanocarrier (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…In mouse xenografts of squamous cell carcinoma (SCC) of the head and neck and breast cancer, the formulation has shown improved tumor control over conventionally administered cisplatin. 1,2 Complementing this enhanced local efficacy, the pharmacokinetic profile of this formulation is superior to intravenously administered cisplatin with a reduced C max but greater area-under-the-curve (AUC), resulting in reduced nephrotoxicity, enhanced local efficacy, and extended systemic tumor cell exposure. 3,4 In a pilot trial of HA-Pt in dogs with spontaneous soft tissue sarcomas, the formulation resulted in similarly favorable tumor and plasma distributions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse xenografts of squamous cell carcinoma (SCC) of the head and neck and breast cancer, the formulation has shown improved tumor control over conventionally administered cisplatin. 1,2 Complementing this enhanced local efficacy, the pharmacokinetic profile of this formulation is superior to intravenously administered cisplatin with a reduced C max but greater area-under-the-curve (AUC), resulting in reduced nephrotoxicity, enhanced local efficacy, and extended systemic tumor cell exposure. 3,4 In a pilot trial of HA-Pt in dogs with spontaneous soft tissue sarcomas, the formulation resulted in similarly favorable tumor and plasma distributions.…”
mentioning
confidence: 99%
“…Compared to cisplatin, HA-Pt significantly decreased tumor burden, prolonged survival rate, and reduced systemic toxicity as indicated by weight loss and pathological analysis in mice. 1,2,8 …”
mentioning
confidence: 99%
“…Recently, a hyaluronan-cisplatin nanoconjugate (HA-Pt) has been developed and demonstrated to be useful in pre-clinical studies for loco-regional therapy of multiple cancers, including head and neck squamous cell carcinoma (16-18), breast cancer (19), melanoma (20), and soft tissue sarcoma (21). Hyaluronan (HA) is an inert, naturally-occurring glycosaminoglycan polysaccharide found in the extracellular matrix of most mammalian connective tissues (22).…”
Section: Introductionmentioning
confidence: 99%
“…In previously published work, there were significantly increased lymphatic tissue concentrations of cisplatin and reduced organ toxicities with peritumoral injections of cisplatin conjugated to nanoscopic (25–100 nM) particles of HA (HA‐cisplatin) compared to systemically delivered standard cisplatin therapy. In related studies investigating this drug in orthotopic murine models, HA‐cisplatin was found to have significantly higher anticancer efficacy in vivo relative to conventional IV cisplatin therapy in HNSCC xenografts implanted in the buccal mucosa of the subject mice …”
Section: Introductionmentioning
confidence: 99%
“…In related studies investigating this drug in orthotopic murine models, HA-cisplatin was found to have significantly higher anticancer efficacy in vivo relative to conventional IV cisplatin therapy in HNSCC xenografts implanted in the buccal mucosa of the subject mice. 3,9 Moreover, HA is also a highly specific ligand for the CD44 surface receptors, 10 and CD44 is described as a cell surface marker specific for CSCs in HNSCC. In fact, CSCs were first successfully isolated from HNSCC cell lines utilizing CD44 expression.…”
Section: Introductionmentioning
confidence: 99%